Emotion perception across cultures: the role of cognitive mechanisms - Engelmann, Jan B.; Pogosyan, Marianna (Frontiers in Psychology, 2013)
Despite consistently documented cultural differences in the perception of facial expressions of emotion, the role of culture in shaping cognitive mechanisms that are central to affect perception has received relatively little attention in past research. We review recent developments in cross-cultural psychology that provide particular insights into the modulatory role of culture on cognitive mechanisms involved in interpretations of facial expressions of emotion through two distinct routes: display rules and cognitive styles. Investigations of affect intensity perception have demonstrated that facial expressions with varying levels of intensity of positive affect are perceived and categorized differently across cultures. Recent findings indicating high levels of differentiation between intensity levels of facial expressions among American participants, as well as deviations from clear categorization of high and low intensity expressions in Japanese and Russian participants, suggest that display rules shape mental representations of emotions, such as intensity levels of emotion prototypes. Furthermore, a series of recent studies using eye tracking as a proxy for overt attention during face perception has identified culture-specific cognitive styles, such as the propensity to attend to very specific features of the face. Together, these results suggest a cascade of cultural influences on cognitive mechanisms involved in interpretations of facial expressions of emotion, whereby cultures impart specific behavioral practices that shape the way individuals process information from the environment. These cultural influences lead to differences in cognitive style, such as attentional biases and emotion prototypes, which partially account for the gradient of cultural agreements and disagreements obtained in past investigations.